Physical, Mechanical and Durability Properties of Soil Building Blocks Reinforced with Synthetic Fibre - Selsiadevi, S; Ramani Sujatha, Evangelin (International Journal of Engineering and Technology, 2018)
Earth construction is the most economic way to solve housing problems, particularly in case of low cost building, with the limitation of resources. The simplicity in production of earth blocks justifies by the availability of soil as raw material and by the less energy in production. Generally, fibre inclusion increases the strength and performance of the earth blocks. Synthetic fibre such as AR glass fibre, polypropylene fibre were used and investigated experimentally with different percentages of fibre 0.25 %, 0.50 %, 0.75 % and 1 % by weight of earth. A sequence of test was conducted with and without addition of fibre to soil building blocks. Physical properties, mechanical properties and durability properties specifically density test, water absorption by capillarity test, linear shrinkage, compressive test, indirect tensile stress, wearing test and erosion test were conducted and compared with different fibre ratio to determine the optimum fibre content in each mix order to produce blocks that will provide the maximum strength.Â